2010
DOI: 10.3109/09513590.2010.507826
|View full text |Cite
|
Sign up to set email alerts
|

Increased leukocyte ABCA1 gene expression in post-menopausal women on hormone replacement therapy

Abstract: The beneficial cardiovascular effects of HRT could be explained, at least in part, by increasing the ABCA1 gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
2
20
1
1
Order By: Relevance
“…The effects on serum lipid composition found after the HRT agree with previous studies [16] and has been discussed earlier by us [9].…”
Section: Blood Sampling and Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…The effects on serum lipid composition found after the HRT agree with previous studies [16] and has been discussed earlier by us [9].…”
Section: Blood Sampling and Analysissupporting
confidence: 91%
“…The mean age at menopause in the population was 46.5±3.7 years. Details of the study design and sampling have been reported earlier [9]. Briefly, Women were considered postmenopausal if they had no menstrual periods for at least 12 months and serum follicle-stimulating hormone (FSH) of >35 IU/L without other obvious pathological or physiological cause.…”
Section: Subjectsmentioning
confidence: 99%
“…Although the cause of sex-related differences is not fully understood, estrogen is known to have an effect in premenopausal women by increasing HDL-C concentrations (37,38). Moreover, there is evidence that estrogen increases ABCA1 expression in different tissues (39,40) and estrogen therapy increases ABCA1 expression in leukocytes and improves lipid profile in menopausal women (41), suggesting that the sexspecific interaction here could be mediated by the effect of estrogen on ABCA1 expression. On the other hand, although testosterone is known to be responsible for lowering HDL-C levels in men (42), this hormone has been found not to affect apoA-I or ABCA1 expression in hepatocytes or human monocyte-derived macrophages (43), which is consistent with the lack of ABCA1-nutrient interaction observed in males.…”
Section: Discussionmentioning
confidence: 99%
“…ABCA1, CCL5 and FASLG have been previously shown to associate with HRT and menopause (Christodoulakos et al, 2007;Darabi, Rabbani et al, 2011;Kangas et al, 2014), and both UHRF1 and PPP2R2B…”
Section: This Analysis Revealed That Five Genes With Dmrs (Abca1 Uhrmentioning
confidence: 99%